2020
DOI: 10.1016/j.physleta.2020.126265
|View full text |Cite
|
Sign up to set email alerts
|

PDM creation and annihilation operators of the harmonic oscillators and the emergence of an alternative PDM-Hamiltonian

Abstract: The exact solvability and impressive pedagogical implementation of the harmonic oscillator's creation and annihilation operators make it a problem of great physical relevance and the most fundamental one in quantum mechanics. So would be the position-dependent mass (PDM) oscillator for the PDM quantum mechanics. We, hereby, construct the PDM creation and annihilation operators for the PDM oscillator via two different approaches. First, via von Roos PDM Hamiltonian and show that the commutation relation between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…2 Further studies in noncommuting quantum spaces led to a Schrödinger equation with a position-dependent effective mass (PDM). 3 Along the last decades, the PDM systems have attracted attention because of their wide range of applicability in semiconductor theory, [4][5][6][7] nonlinear optics, 8 quantum liquids, 9,10 inversion potential for NH 3 in density functional theory, 11 particle physics, 12 many body theory, 13 molecular physics, 14 Wigner functions, 15 relativistic quantum mechanics, 16 superintegrable systems, 17 nuclear physics, 18 magnetic monopoles, 19,20 astrophysics, 21 nonlinear oscillations, [22][23][24][25][26][27][28][29][30][31] factorization methods and supersymmetry, [32][33][34][35][36] coherent states, [37][38][39] etc.…”
Section: Introductionmentioning
confidence: 99%
“…2 Further studies in noncommuting quantum spaces led to a Schrödinger equation with a position-dependent effective mass (PDM). 3 Along the last decades, the PDM systems have attracted attention because of their wide range of applicability in semiconductor theory, [4][5][6][7] nonlinear optics, 8 quantum liquids, 9,10 inversion potential for NH 3 in density functional theory, 11 particle physics, 12 many body theory, 13 molecular physics, 14 Wigner functions, 15 relativistic quantum mechanics, 16 superintegrable systems, 17 nuclear physics, 18 magnetic monopoles, 19,20 astrophysics, 21 nonlinear oscillations, [22][23][24][25][26][27][28][29][30][31] factorization methods and supersymmetry, [32][33][34][35][36] coherent states, [37][38][39] etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we have shown that DDL quantum systems can reflect infinite distinct discrete energy levels under suitable form of position dependent mass. The model mass [15] and used by others [1,3,7,9]. It is worth mentioning that only this typical form of T can be derived [8].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for N=1 model Hamiltonian was also previously proposed by Mathews and Lakshnman for the study of nonlinear analysis in view of its potential applications in quantum field theory [4]. As such the Hamiltonian is not self-adjoint(H P DM ̸ = H † P DM ) [1,3,7,9,[13][14][15]. In its self adjoint form, it is expressed as [15]:…”
Section: Position Dependent Mass System Without Potential Changementioning
confidence: 99%
“…As mentioned in the Introduction, §1, the nature of the problem or potential function considered determines the type of mass variation functions to be employed [14]. For instance, m ( x ) can be a quadratic or exponential function of position x [20,102,103]. The former has been classified on the basis of its singularity property: as either regular mass-functions without singularity or as singular mass-functions with single or dual singularities [20].…”
Section: Position-dependent Mass Oscillatorsmentioning
confidence: 99%